2019
DOI: 10.18494/sam.2019.2494
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Scattering in Ni Wires Fabricated on Ferroelectric LiNbO3 Substrate for Magnetic Sensor Application

Abstract: We investigated the magnetoresistive property of a micrometer-scale Ni wire with a uniaxial magnetic anisotropy induced by the formation of a heterojunction between a Ni layer and a single-crystal lithium niobate (LiNbO 3) substrate. We revealed that the domain structure can be controlled by adjusting the wire alignment and that its magnetoresistance (MR) is dependent on the magnetic domain structure as well as the reversal process. The introduction of a heterojunction is a crucial method of controlling the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
(65 reference statements)
2
4
0
Order By: Relevance
“…We found that uniaxial magnetic anisotropy was induced in the Ni layer on the LiNbO 3 substrate due to the formation of the heterojunction; the uniaxial magnetic anisotropy forced the Ni magnetizations to stochastically align parallel or antiparallel to the X -axis of the LiNbO 3 substrate (indicated by an arrow in region (i) of Figure 1 b). As previously reported [ 33 , 34 , 35 , 36 , 37 , 38 ], a stripe domain structure is naturally formed when the wire is aligned perpendicular to the X -axis of the LiNbO 3 substrate, even in the absence of an external magnetic field, due to the competition between magnetic shape anisotropy and uniaxial magnetic anisotropy induced by the heterojunction (region (ii) of Figure 1 b) [ 33 , 34 , 35 , 36 , 37 , 38 ]. The magnetic domain width is dependent on the width of wire, being almost equal to the width of the wire.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…We found that uniaxial magnetic anisotropy was induced in the Ni layer on the LiNbO 3 substrate due to the formation of the heterojunction; the uniaxial magnetic anisotropy forced the Ni magnetizations to stochastically align parallel or antiparallel to the X -axis of the LiNbO 3 substrate (indicated by an arrow in region (i) of Figure 1 b). As previously reported [ 33 , 34 , 35 , 36 , 37 , 38 ], a stripe domain structure is naturally formed when the wire is aligned perpendicular to the X -axis of the LiNbO 3 substrate, even in the absence of an external magnetic field, due to the competition between magnetic shape anisotropy and uniaxial magnetic anisotropy induced by the heterojunction (region (ii) of Figure 1 b) [ 33 , 34 , 35 , 36 , 37 , 38 ]. The magnetic domain width is dependent on the width of wire, being almost equal to the width of the wire.…”
Section: Introductionsupporting
confidence: 79%
“…The drastic change in the magnetoresistance effect of the Ni wires elongated perpendicular and parallel to the X -axis of the LiNbO 3 substrate, as shown in Figure 4 of Ref. [ 36 ], reflected the unusual domain structures, as observed in Figure 1 .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This investigation enabled us to understand the magnetic field dependence of magnetization reversal behavior associated with stripe domain structure formation and domain wall displacement. 16,17,70) To evaluate the magnetism of this system through the electric measurements, a ground-signal-ground-type microwave probe was connected to the CPW electrode. The magnetoresistance (MR) was measured using the lock-in detection technique and the rectifying effect is detected by a bias-tee circuit and a voltmeter as shown in Fig.…”
Section: Fabrication Of the Sample And Measurement Setupmentioning
confidence: 99%